2021
DOI: 10.3389/fnut.2021.710555
|View full text |Cite
|
Sign up to set email alerts
|

Red and White Meat Intake in Relation to Mental Disorders in Iranian Adults

Abstract: Background: The association between meat consumption and mental disorders is less investigated in Iranian population. We examined the association between meat consumption and prevalence of symptoms of depression, anxiety, and psychological distress in Iranian adults.Methods: This cross-sectional study included 3,362 participants aged 18–55 years old. A dish-based 106-item semiquantitative food frequency questionnaire (FFQ) was used to assess usual dietary intake of study population. Hospital Anxiety and Depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…In a study by Mofrad et al women in the highest quartile of red meat consumption compared with those in the lowest quartile had a highest prevalence of depressive symptoms, anxiety and stress (41). In contrast, the results of a study published in 2021, showed no any association between red meat consumption and mental disorders in women (42). Moreover, Chi et al in a prospective study, did not nd any relationship between red meat and poultry consumption with the risk of depression in postmenopausal women (43).…”
Section: Discussionmentioning
confidence: 93%
“…In a study by Mofrad et al women in the highest quartile of red meat consumption compared with those in the lowest quartile had a highest prevalence of depressive symptoms, anxiety and stress (41). In contrast, the results of a study published in 2021, showed no any association between red meat consumption and mental disorders in women (42). Moreover, Chi et al in a prospective study, did not nd any relationship between red meat and poultry consumption with the risk of depression in postmenopausal women (43).…”
Section: Discussionmentioning
confidence: 93%
“…Our findings are in line with a previous case-control study, which showed that higher intake of red meat (calculated by summing up the intake of red meat, processed meat, and animal offal) was associated with increased risk of depressive symptoms (odds ratio Q 4 vs. Q 1 = 1.43; 95% CI: 1.09–1.89, P for trend = 0.02). 32 In this study, however, they did not individually assess the association between animal offal intake and the risk of depressive symptoms.…”
Section: Discussionmentioning
confidence: 93%
“…Likewise, this study observed more moderate and poor mental health issues in participants who consumed red meat more than twice daily. Red meat consumption was associated with an increased risk of depressive symptoms, especially among men and those of normal weight, whereas white meat consumption was associated with a decreased risk of depression (42).…”
Section: Association Of Protein Intake On Health-related Qualities Of...mentioning
confidence: 93%